'Preston Strike News', 10 May, 1926 (Preston, 1926)
1926 1918-1939 "'Preston Strike News', 10 May, 1926" [T0126.jpg], 1926, Preston Central Strike Committee General Strike, 'Preston Strike News', 10 May, 1926. This daily news bulletin, in common with hundreds of others produced by local strike committees around the country contained a mixture of local and national news, the latter passed on by TUC despatch riders.